Psychometric evaluation of the Asthma Diary Usability Questionnaire (ADU-Q): An adaptation and validation of a usability assessment tool among adults with Asthma - Sharifah Idayu Sayid Abdullah; Nik Munirah Nik Mohd Nasir; Lina Lohshini Kanoo; Nur Amirah Shibraumalisi (PLoS ONE, 2026)
The asthma diary has been established as a self-management tool to help patients achieve good disease control. However, asthma diary compliance is low, indicating a need to assess the diary’s usability. Given the scarcity of a validated tool for assessing asthma diary usability, this study aims to adapt the Malay version of the mHealth App Usability Questionnaire (M-MAUQ) into the Asthma Diary Usability Questionnaire (ADU-Q) (Malay) and to assess its psychometric properties. In the first phase, the M-MAUQ items were adapted and rearranged into the four domains of the Nielsen usability model. In the second phase, content validity was assessed in two stages: domain validation by 3 experts, followed by item content validation by 7 experts. Face validation was then conducted by 10 patients with asthma. In the third phase, a cross-sectional study of 115 asthma patients attending the primary care clinic and the respiratory clinic follow-up was conducted. All patients completed the ADU-Q (Malay), and 62 patients were contacted 2 weeks later to complete the ADU-Q again. Exploratory factor analysis was performed with promax rotation, while reliability was assessed using Cronbach’s alpha and the intraclass correlation coefficient. The item content validity index was 1.0, and item face validity indices ranged from 0.9 to 1.0. Exploratory factor analysis identified a three-factor structure with factor loadings >0.5 for all items; corrected item–total correlations exceeded 0.5, Cronbach’s alpha was 0.982, and the intraclass correlation coefficient was 0.988, demonstrating excellent internal consistency and test–retest reliability. Based on these findings, ADU-Q is a valid, reliable and stable tool for assessing the usability of an asthma diary among adults with asthma.